Electromagnetic navigation bronchoscopy fluorescence localization and VATS subxiphoid bilateral wedge resection under non-intubated anesthesia - He, Jiaxi; Yang, Hanyu; He, Jianxing; Li, Shuben (Journal of Thoracic Disease, 2019)
Computed tomography guided (CT guided) methylene blue or medical glue injection is the prevailing methods for bilateral pulmonary sub-solid nodules (SSN). Most of the bilateral SSNs are treated by surgeries on either side in different period.